Fertility Preservation in Female Pediatric Patients With Cancer: A Clinical and Regulatory Issue - Brancati, Serena; Gozzo, Lucia; Longo, Laura; Vitale, Daniela Cristina; Russo, Giovanna; Drago, Filippo (Frontiers in Oncology, 2021)
Fertility preservation represents one important goal of cancer patients’ management due to the high impact on health and quality of life of survivors. The available preventive measures cannot be performed in all patients and are not feasible in all health-care facilities. Therefore, the pharmacological treatment with GnRHa has become a valuable non-invasive and well-tolerated alternative, especially in those who cannot access to cryopreservation options due to clinical and/or logistic issues. Supporting data demonstrate a significant advantage for the survivors who received GnRHa in the long-term maintenance of ovarian function and preservation of fertility. The prevention of the risk of ovarian failure with GnRHa is a typical off-label use, defined as the administration of a medicinal product not in accordance with the authorized product information. Italy has officially recognized the off-label use of GnRHa in adult women at risk of premature and permanent menopause following chemotherapy. However, fertility preservation still represents an unmet medical need in adolescents who cannot access to other treatment options.